Intertextual voices and engagement in tv advertisements - Feng, D.; Wignell, Peter (2011)
By analysing multimodal TV advertisements, this study aims to show how intertextual voices are exploited in advertising discourse to enhance persuasive power. Taking as their point of departure the assumption that all discourses are intertextual recontextualizations of social practice that draw on external voices from both specific discourses and discursive conventions, the authors identify two types of intertextual voice in TV advertisements: character and discursive voice. This article illustrates the multimodal construction of voices and demonstrates that the choice of voices is closely related to the 'domain' of the product. It is argued that the intertexual voices contribute to the advertising discourse through multimodal engagement strategies. Character voice endorses the advertised product through such resources as lexico-grammar, intonation, facial expression and staged narrative, while discursive voice endorses the advertised product through contextualization and intertextual discourse structure. It is hoped that the study will shed light on the understanding of the heteroglossic nature of advertisements, the interaction between intertextual voices and the advertised message, and multimodal construction of voices and engagement. © The Author(s), 2011.